2023
DOI: 10.1093/jphsr/rmad014
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude towards antibiotic use and resistance among Arab population: a questionnaire-based study of 11 countries from the Middle East and North Africa

Abstract: Objectives Antibiotic usage has evolved over the years among the Arab population, and it has also gone under misuse resulting in the development of antimicrobial resistance (AMR). Therefore, the current study aimed to address this issue by evaluating the level of knowledge and attitude of Arab population towards antibiotic usage and AMR to develop a pathway to reduce the risk of antibiotic resistance. Methods A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
2
2
1
Order By: Relevance
“…Residents of rural areas, females, participants with large family sizes, married, illiterate, and farmer participants had a very low level of knowledge compared to the other respective categories. Educational level, which is a very important sociodemographic factor, has been reported as an important predicting factor for the level of knowledge on antibiotic use and resistance in community-based studies by Karuniawati et al [ 18 ], Gebeyehu et al [ 20 ], Sindato et al [ 30 ], Hassan et al [ 56 ], and Di et al [ 58 ], which are in line with our results. Regarding the gender, Simegn et al [ 36 ] also reported that females had poor knowledge than males, which is in line with our result.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Residents of rural areas, females, participants with large family sizes, married, illiterate, and farmer participants had a very low level of knowledge compared to the other respective categories. Educational level, which is a very important sociodemographic factor, has been reported as an important predicting factor for the level of knowledge on antibiotic use and resistance in community-based studies by Karuniawati et al [ 18 ], Gebeyehu et al [ 20 ], Sindato et al [ 30 ], Hassan et al [ 56 ], and Di et al [ 58 ], which are in line with our results. Regarding the gender, Simegn et al [ 36 ] also reported that females had poor knowledge than males, which is in line with our result.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the chi-square test, all sociodemographic characteristics, except that of family size, showed a significant association with the level of knowledge. It is well documented that sociodemographic factors highly influence the level of knowledge regarding antibiotic use and related issues [ 18 , 30 , 56 , 58 ], and the result of this study is thus in line with previous studies. Regarding attitude, all sociodemographic factors, except for the sex of the respondents, were significantly associated with the level of attitude.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Approximately 25% of respondents believed antibiotics could treat viral infections, and there was a misconception that antibiotics always remain effective for treating the same infection in the future [ 18 ]. Another large study conducted Arab populations involving 11 Arabic country reported poor knowledge of antibiotic usage and AMR [ 19 ].…”
Section: Discussionmentioning
confidence: 99%